Historical Demographic Processes Dominate Genetic Variation in Ancient Atlantic Cod Mitogenomes - Martínez-García, Lourdes; Ferrari, Giada; Oosting, Tom; Ballantyne, Rachel; van der Jagt, Inge; Ystgaard, Ingrid; Harland, Jennifer; Nicholson, Rebecca; Hamilton-Dyer, Sheila; Baalsrud, Helle Tessand; Brieuc, Marine Servane Ono; Atmore, Lane M.; et al. (Frontiers in Ecology and Evolution, 2021)
Ancient DNA (aDNA) approaches have been successfully used to infer the long-term impacts of climate change, domestication, and human exploitation in a range of terrestrial species. Nonetheless, studies investigating such impacts using aDNA in marine species are rare. Atlantic cod (Gadus morhua), is an economically important species that has experienced dramatic census population declines during the last century. Here, we investigated 48 ancient mitogenomes from historical specimens obtained from a range of archeological excavations in northern Europe dated up to 6,500 BCE. We compare these mitogenomes to those of 496 modern conspecifics sampled across the North Atlantic Ocean and adjacent seas. Our results confirm earlier observations of high levels of mitogenomic variation and a lack of mutation-drift equilibrium—suggestive of population expansion. Furthermore, our temporal comparison yields no evidence of measurable mitogenomic changes through time. Instead, our results indicate that mitogenomic variation in Atlantic cod reflects past demographic processes driven by major historical events (such as oscillations in sea level) and subsequent gene flow rather than contemporary fluctuations in stock abundance. Our results indicate that historical and contemporaneous anthropogenic pressures such as commercial fisheries have had little impact on mitogenomic diversity in a wide-spread marine species with high gene flow such as Atlantic cod. These observations do not contradict evidence that overfishing has had negative consequences for the abundance of Atlantic cod and the importance of genetic variation in implementing conservation strategies. Instead, these observations imply that any measures toward the demographic recovery of Atlantic cod in the eastern Atlantic, will not be constrained by recent loss of historical mitogenomic variation.